Upaya Meningkatkan Hasil Belajar Siswa Melalui Penggunaan Media Diorama Pada Tema Daerah Tempat Tinggalku Kelas IV SD Negeri 104305 Pergulaan - Nurmala Dewi; Dinda Yarshal (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The purpose of this study is to see whether the use of diorama media can successfully improve student learning outcomes as a learning medium. This study uses a class action research method (CAR). This research was conducted in three cycles. From the results of the research conducted, it shows that the use of diorama media can improve student learning outcomes. Improved learning outcomes occur in each cycle. In the first cycle of learning, student learning outcomes obtained a learning value that was carried out by a 58% completeness score test. In cycle II obtained a completeness level of 68%. Whereas in cycle III students obtained a completeness level of 79% which was in accordance with what was desired. Thus, it can be said that the application of diorama media can improve student learning outcomes on the theme of the area where I live.